Acute Myocardial Infarction During Regadenoson Myocardial Perfusion Imaging. Issue 6 (7th March 2013) - Shah, Sachil; Parra, David; Rosenstein, Robert S.
<x xml:space="preserve">Abstract</x> Pharmacologic stress testing uses vasodilators to provide objective evidence of myocardial ischemia. Adenosine and dipyridamole are nonselective adenosine receptor agonists that have been associated with myocardial infarction (MI) during intravenous infusion. Mechanisms postulated for this effect include coronary steal, transmural steal, global hypotension, and direct vasoconstriction. Regadenoson, a direct A2A agonist, was approved for use in stress testing in 2008. We describe a 68‐year‐old man who presented to our institution with typical angina, relieved by nitroglycerin. He did not have electrocardiogram (ECG) changes suggestive of myocardial pathology, and laboratory testing did not reveal a significant rise in troponin‐I levels. To further assess the etiology of his symptoms, he underwent a pharmacologic stress test with regadenoson followed by technetium 99 m sestamibi. Six minutes after regadenoson infusion, the patient developed severe retrosternal chest pain accompanied by ST elevations on ECG. Sublingual nitroglycerin was administered that resolved both the pain and ECG changes. The patient subsequently underwent urgent coronary angiography and was found to have a 95% critical stenosis involving the left anterior descending artery. We conclude this case represents a MI secondary to coronary steal phenomenon induced by regadenoson infusion. Clinicians should be aware this adverse effect can occur despite the improved side‐effect profile of regadenoson. Continuous monitoring of vital signs and the ECG with regular assessment of symptoms is imperative to identify this rare but potentially devastating adverse event.